The Geographical Mobility of Unemployed Workers: Evidence from West Germany - Melanie Arntz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Using a competing-risk framework of exiting unemployment to jobs in a local or a distant labor market area, this paper investigates whether unemployed individuals in West Germany choose search strategies that favor migrating out of declining regions. Moreover, the paper investigates how such search strategies are affected by the local accommodation of labor market programs. Such programs have been suggested to lead to a regional locking-in effect. Empirical results are obtained from a stratified Cox partial likelihood proportional hazards model that allows for location-specific fixed effects and are compared to estimates from a parametric log-logistic hazard model that takes account of unobserved individual heterogeneity. The findings indicate that unemployed in West Germany are responsive to local labor market conditions and are more likely to leave regions with unfavorable re-employment opportunities. No locking-in effect from labor market programs is found. The probability of migration is found to increase with search time.
Keywords: R23; J64; J62; 330; interregional mobility; unemployment duration; competing-risk; active labor market policy; unobserved location-specific heterogeneity; Arbeitsuche; Arbeitslosigkeit; Regionale Arbeitsmobilität; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Alte Bundesländer; Deutschland